Strategi Pengembangan Kesatuan Pengelolaan Hutan Lindung (KPHL) Flores Timur - Melewanto Patabang; Hardjanto Hardjanto (Faculty of Forestry Universitas Gadjah Mada, 2023)
The Flores Timur FMU establishment was part of the broader efforts to enhance forest governance, improve management practices, and resolve land tenure conflicts effectively within forest areas. However, the challenges commonly encountered included conflicts with communities and other sectors regarding land tenure, area planning, and policy implementation. This research aimed to identify strategic variables of internal and external factors to determine a development strategy for Flores Timur FMU-Protected using SWOT (strengths, weaknesses, opportunities, threats) analysis. The results showed that the primary strategy for managing Flores Timur FMU included law enforcement for forest protection, acceleration of rehabilitation efforts for forests and lands classified as critical, and calculation of forest economic values based on the benefits of environmental services. Moreover, increasing community participation in forest utilization through social forestry programs and employing a participatory approach to forest area boundaries would contribute to effective management.